Advancing Sustainability in Media Education through Ecomedia Literacy - Daou, Perla (2024)
Education for sustainable development is a marginalized topic within the field of media education. However, ecomedia literacy lies at the intersection of critical media literacy and sustainable education pedagogies (Lopez 2015). Ecomedia literacy provides a framework for educators to teach students how to critically access, analyze, evaluate, and create media from an ecologically sustainable point of view, which consequently provides an opportunity for social transformation. Ecomedia literacy raises awareness of the interconnectedness media has with our environment that could be categorized into ecological footprint and ecological mindprint (Lopez 2015). Ecological footprint encompasses teaching about toxic modes of extraction and production of media materials from the earth’s commons while ecological mindprint teaches about the different environmental ideologies, perceptions, and attitudes that the media perpetuates towards the environment (Lopez 2015; 2020). This chapter details an educational project that implemented ecomedia literacy through a critical pedagogy approach in Lebanon (Daou, forthcoming). The ecomedia literacy curriculum developed includes two case studies from a Lebanese context and a learning platform that was built to pilot the curriculum in two undergraduate classes. After presenting the results of the data collected on the curriculum through qualitative pre-and post-surveys, this chapter will present the findings on the usefulness, applicability, and relevance of the curriculum. In conclusion, this chapter recommends that ecomedia literacy provides an educational tool for ecological social transformation within Lebanon, the Arab region, and beyond as one means of achieving the UN’s sustainability development goals (SDGs).